If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -50 = 3x + -14 Reorder the terms: -50 + 5x = 3x + -14 Reorder the terms: -50 + 5x = -14 + 3x Solving -50 + 5x = -14 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -50 + 5x + -3x = -14 + 3x + -3x Combine like terms: 5x + -3x = 2x -50 + 2x = -14 + 3x + -3x Combine like terms: 3x + -3x = 0 -50 + 2x = -14 + 0 -50 + 2x = -14 Add '50' to each side of the equation. -50 + 50 + 2x = -14 + 50 Combine like terms: -50 + 50 = 0 0 + 2x = -14 + 50 2x = -14 + 50 Combine like terms: -14 + 50 = 36 2x = 36 Divide each side by '2'. x = 18 Simplifying x = 18
| X^2/3=1 | | f(x)=10x+15 | | -10(1-11n)+11n=13(8n+11) | | -2d=-2d+9 | | 5(2X+8)=150 | | (-4)=6x-5 | | n^7+2n^2+1=0 | | 70000-89= | | f(3)=8x-24ln(x) | | (5x-2)(5x+3)= | | -9v-2v-18=26 | | 6x+4y-12=0 | | 111-989= | | ln(2x-6)=ln(7) | | 40=-2/5x=22 | | 6(-13p+5)=-6-6(8p-1) | | 0.03x^2-0.5x+0.06=0 | | 8x+66+2x+120=180 | | t^2h+3t=0 | | 4n+16=60 | | (x^4+9x^3+20x^2+13x+6)=(x+6) | | F(-4)=6x-5 | | 9-3k+4= | | -19y=2y+9-6y | | 3/2x=-6 | | x*2-x-12=0 | | 3(2x-7)-4=7-5(4-3x) | | X+44=3 | | 4000-400x=1600 | | t/3-2=2 | | 2x+-10=3x+15 | | 3x-4y+5=2x-5y-6 |